Flow of viscoelastic fluid with microrotation at a boundary layer flow of a horizontal circular cylinder - Laila Amera, Aziz; Abdul Rahman, Mohd Kasim; Mohd Zuki, Salleh; Faye, Ibrahim (Penerbit Akademia Baru, 2022)
In this study, the dynamics of the non-Newtonian viscoelastic fluid with microrotation at a boundary layer of a horizontal circular cylinder is investigated. For this case, Lorentz force is induced by external magnetic field positioned at right angle of the fluid flow, hence the magnetohydrodynamic effect is embedded in the momentum equation of the proposed model in addition to other governing parameters. The constitutive equations are converted to dimensionless form along with the associated boundary conditions before the resulting partial differential equations are solved using finite difference technique in Fortran programming. Results are validated before the velocity and microrotation profiles are examined and the effects of material, viscoelastic and magnetohydrodynamic parameter on the flow is discussed.